Penggunaan abu bakaran klinikal di dalarn konkrit prestasi tinggi - Mardalena,; Muhammad Fauzi Mohd. Zain,; Hassan Basri, (2003)
The use of waste materials such as municipal solid waste, industrial waste, and hospital waste for beneficial purposes is an appropriate choice, because it will reduce the need for landfill space. To reduce the volume of materials waste, the most effective method is incineration. It can reduce the volume of waste up to 90% and will produce two by-products, namely bottom-ash and fly ash. This research uses fly ash from Tongkah Medivest Sdn. Bhd. clinical waste incinerator as clinical ash. It is used as cement replacement material at 5%, 10%, 15%, 20%, 25%, 30%, and 35% for making high performance concrete. The concrete were designed at water-binder ratio of 0.35 and 0.50. Water curing and air curing were practised. Compressive strengths were determined at the age of 7, 14, 28, 56, 90, and 180 days. The result showed that the compressive strength of 0.35 water-binder ratio under both curing methods produced higher strength. The compressive strengths of concrete were decreased as the percentage of clinical ash increased. The concrete that contained 5% clinical ash showed the highest value of compressive strength compared to others. Therefore, from the perspective of compressive strength, clinical ash can be used in concrete